Water quality assessment in a shallow lake used for tourism - Dembowska Ewa A.; Pul Patrycja L. (Limnological Review, 2015)
The routine evaluation of water quality is limited to lakes with the largest area. In Poland, only lakes with an area exceeding 50 hectares are monitored by the State Environmental Monitoring System. For many local communities, however, small lakes are more important. This applies mainly to areas with a small number of lakes, where even the smallest lakes are used for various purposes. This paper presents the results of phytoplankton analysis in a small and shallow lake used for recreation. The study was conducted at three sites located in different parts of the lake. A total of 122 algae taxa were identified in the phytoplankton, mainly diatoms and green algae. The most constant taxa in the lake were: Stephanodiscus hantzschii, Desmodesmus communis, Pediastrum tetras and Crucigenia tetrapedia. The average phytoplankton biomass was 37 mg l−1. The maximum biomass, almost 140 mg dm−3, was recorded in late July at the site located near the beach. At that time, there was a massive cyanobacterial bloom composed of Microcystis wesenbergii and Aphanizomenon issatschenkoi. Based on these studies, the lake should be classified as hypertrophic with bad ecological status. This lake should not be used for recreational purposes in the current state.